2021
DOI: 10.1016/j.meegid.2021.104831
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology analysis of early variants of SARS-CoV-2 reveals the potential impact of mutations P504L and Y541C (NSP13) in the clinical COVID-19 outcomes

Abstract: Since severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused global pandemic with alarming speed, comprehensively analyzing the mutation and evolution of early SARS-CoV-2 strains contributes to detect and prevent such virus. Here, we explored 1962 high-quality genomes of early SARS-CoV-2 strains obtained from 42 countries before April 2020. The changing trends of genetic variations in SARS-CoV-2 strains over time and country were subsequently identified. In addition, viral genotype mapping and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The question of the differences in clinical courses—specifically, in disease severity and outcome—between the different SARS-CoV-2 variants has been studied extensively [ 18 , 19 , 20 , 21 , 22 ]. By undergoing mutations in genes responsible for the expression of viral proteins (specifically, spike and nucleocapsid proteins), the SARS-CoV-2 virion changes its properties, e.g., its ability to infect new cells, to further reproduce, and to evade host immune responses [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The question of the differences in clinical courses—specifically, in disease severity and outcome—between the different SARS-CoV-2 variants has been studied extensively [ 18 , 19 , 20 , 21 , 22 ]. By undergoing mutations in genes responsible for the expression of viral proteins (specifically, spike and nucleocapsid proteins), the SARS-CoV-2 virion changes its properties, e.g., its ability to infect new cells, to further reproduce, and to evade host immune responses [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three studies (one bigdata analysis [50] and two clinical studies [17,51]) reported that the SARS-CoV-2 variants were significantly associated with decrease in severity of disease. The remaining 27 studies (one animal study [18], 22 bigdata analyses [8][9][10][11][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] and four clinical studies [70][71][72][73]) described the positive association between the different variants with severity of COVID-19 (Table 3). A clinical study by Long et al showed that infection with SARS-CoV-2 variants harboring the D614G substitution was not associated with disease severity, overall mortality, transfer to ICU, mechanical ventilation and length of stay at hospital [41].…”
Section: Relation Between Viral Mutations and Severity Of Covid-19 Infectionmentioning
confidence: 99%
“…Major NSPs are 3, 5, 12, and 13 shown in Figure 1. Frequency of variation in >1900 SARS-CoV-2 genome samples examined varied from 5.48 in coding regions to 6.96 in the noncoding regions [18]. The variation sites included S: 23403 (D614G), ORF1ab: 14408 (NSP12b: P314L),17747 (NSP13: P504L) and 17858 (NSP13:Y541C), and ORF8: 28144 (L84S).…”
Section: Genome Organisation Of Sars-cov-2mentioning
confidence: 99%